2019
DOI: 10.1002/jcb.28441
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic genes of hepatocellular carcinoma based on gene coexpression network analysis

Abstract: Hepatocellular carcinoma (HCC) is the most common subtype in liver cancer whose prognosis is affected by malignant progression associated with complex gene interactions. However, there is currently no available biomarkers associated with HCC progression in clinical application. In our study, RNA sequencing expression data of 50 normal samples and 374 tumor samples was analyzed and 9225 differentially expressed genes were screened. Weighted gene coexpression network analysis was then conducted and the blue modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…C1RL had not been mentioned in cancer until a report indicating signi cant associations of non-Hodgkin lymphoma and diffuse large B-cell lymphoma with the C1RL gene in 2012 [15]. In recent years, C1RL has been reported to be a prognostic biomarker in hepatocellular carcinoma [13] and renal cell cancer [14]. Our results showed evidence that C1RL is highly expressed in glioma samples and predicts a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…C1RL had not been mentioned in cancer until a report indicating signi cant associations of non-Hodgkin lymphoma and diffuse large B-cell lymphoma with the C1RL gene in 2012 [15]. In recent years, C1RL has been reported to be a prognostic biomarker in hepatocellular carcinoma [13] and renal cell cancer [14]. Our results showed evidence that C1RL is highly expressed in glioma samples and predicts a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
“…Complement C1r subcomponent like (C1RL) was found to be a prognostic marker in hepatocellular carcinoma [13] and renal cell cancer [14]. A gene-based analysis showed signi cant associations between non-Hodgkin lymphoma or diffuse large B-cell lymphoma and the C1RL gene [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we tried to establish a prognosis/diagnosis-associated mRNA-miRNA-lncRNA ceRNA triple sub-network in hepatocellular carcinoma. By performing survival (OS and RFS) analysis using TCGA hepatocellular carcinoma data, nine genes including three novel genes (CELSR3, GPSM2 and CHEK1) and six "known" genes [CLEC3B (26), DNASE1L3 (27), PTTG1 (28,29), KIF2C (30), XPO5 (31,32) and UBE2S (33,34)] were identified as prognosisassociated genes in hepatocellular carcinoma. The prognostic values of the three novel genes in hepatocellular carcinoma have not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…By intersecting OS-associated genes and RFSassociated genes, 9 genes (CLEC3B, DNASE1L3, PTTG1, CELSR3, GPSM2, KIF2C, XPO5, UBE2S, and CHEK1) were defined as candidate genes, which were commonly appeared in OS-associated gene set and RFS-associated gene set ( Figure 1A). After reviewing the published literatures and previous studies, we found that 6 of 9 genes [CLEC3B (26), DNASE1L3 (27), PTTG1 (28,29), KIF2C (30), XPO5 (31,32), and UBE2S (33,34)] have been demonstrated to act as promising prognostic biomarkers for hepatocellular carcinoma. The rest three genes (CELSR3, GPSM2, and CHEK1) have not been studied for their prognostic values in hepatocellular carcinoma so far.…”
Section: Celsr3 Gpsm2 and Chek1 Were Identified As Three Novel Progmentioning
confidence: 98%
“…Finally, in Xu et al [29] (2019), Xu et al study Hepatocellular carcinoma, a very common subtype of liver cancer. The authors conducted a WGCNA to identify complex gene interactions that affect prognosis.…”
Section: Related Workmentioning
confidence: 99%